The Performance of Islamic Nasep Music in Bangkok - Binson, Bussakorn (Journal of Urban Culture Research, 2022)
This research focuses on the Nasep performance of the Zainub band in Bangkok, regards its background, band administration and knowledge transmission including Islamic views on music performance. Results have shown that Nasep, which originated from Nasheed and Li-ke Riab is the performing art of Muslims in central Thailand. The Zainub band, where most members are women is a gathering of award winning Qaris1 and its main presentation is Arab-Malay songs. Musical knowledge has been transmitted by rote and is self-taught. The band members uphold the view that singing and playing music are allowed as long as they do not violate Islamic morals. The main instruments are three types of drums; Doumbek, Cajon and Bongos along with a violin and accordion. The performances of the Zainub band embody the characteristics of cultural integration. Modern media technologies are adopted to meet the audiences’ preferences while still maintaining their cultural identity, traditions and beliefs.